Plastic recovery and self-healing in longitudinally twinned SiGe nanowires. Issue 18 (24th April 2019) - Shikder, Md Ruhul Amin; Ramasubramanian, Ajaykrishna; Maksud, Mahjabin; Yurkiv, Vitaliy; Yoo, Jinkyoung; Harris, Charles T.; Vasudevamurthy, Gokul; Mashayek, Farzad; Subramanian, Arunkumar
Abstract : This article presents self-healing and mechanical stabilization in longitudinally-twinned SiGe nanowires through segmented elastic and plastic deformation within their grains. Abstract : This paper reports on plastic recovery and self-healing behavior in longitudinally-twinned and [112] orientated SiGe nanowire (NW) beams when they are subjected to large bending strains. The NW alloys are comprised of lamellar nanotwin platelet(s) sandwiched between two semi-cylindrical twins. The loading curves, which are acquired from atomic force microscope (AFM) based three-point bending tests, reveal the onset of plastic deformation at a characteristic stress threshold, followed by further straining of the NWs. This ductility is attributed to dislocation activity within the semi-cylindrical crystal portions of the NW, which are hypothesized to undergo a combination of elastic and plastic straining. On the other hand, the lamellar nanoplatelets undergo purely elastic stretching. During the unloading process, the release of internal elastic stresses enables dislocation backflow and escape at the surface. As a result, the dislocations are predominantly annihilated and the NW samples evidenced self-healing via plastic recovery even at ultra-large strains, which are estimated using finite-element models at 16.3% in one of the tested devices. Finite element analysis also establishes the independence of the observed nanomechanical behavior on the relative orientation of the load with respect to the nanoplatelet. This first observation of reversible plasticity in the SiGe material system, which is aided by a concurrent evolution of segmented elastic and plastic deformation within its grains during the loading process, presents an important new pathway for mechanical stabilization of technologically important group-IV semiconductor nanomaterials.